Multimode coupling of modes model for spurious responses on SiO2/LiNbO3 substrate. (19th June 2018) - Goto, Rei; Fujiwara, Joji; Nakamura, Hiroyuki; Hashimoto, Ken-ya
Abstract: The temperature-compensated surface acoustic wave (TC-SAW) is widely studied to achieve the tight roll-off characteristics required for mobile communication systems. LiNbO3 covered with a SiO2 film structure is proposed for one of the temperature compensation methods. One of the issues with applying the SiO2 /LiNbO3 substrate for filter devices is the prediction of spurious responses. These spurious responses are caused by the interaction of the different propagation Rayleigh mode and shear horizontal (SH) mode. In this paper, the extended coupling of modes (COM) model can be expressed and the mutual coupling between SH and Rayleigh modes is proposed. To verify the proposed multimode COM model, the transmission characteristics were simulated and compared with the measurement results.